Management of Violence on Children in the Education World to Improve the Quality of Schools - Akmaluddin, Akmaluddin; Mardhatillah, Mardhatillah; Rahmattullah, Rahmattullah; Sari, Siti Mayang; Siregar, Marlina; Ayu, Al Fajri Kamal (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The purpose of this research was to find out the prevention and control of violence and the management of supervision of violence in the world of education for students in improving the quality of schools. This research used the method of descriptive research in terms of survey research. The subjects of this study were school residents (principals, teachers, and school staff at SD Aceh Besar. To collect factual information is used the interview method. The use of interviewing techniques received positive responses, as well as providing input and effective suggestions regarding the management of violence monitoring in the field of education. The results of this study show that there are several indicators in the monitoring management of violence. First, schools must conduct counseling or outreach and work with the police officer. Next, violence management can also be carried out in an orderly manner and create a conducive or comfortable situation by forming a violence monitoring team, implementing the rules and sanctions, or follow-up when the event of violence. Research conclusions show some internal indicators of management violence supervision: schools should take counseling or socialization and work with government officials such as the police.